The importance of perfusion index monitoring in evaluating the efficacy of stellate ganglion blockage treatment in Raynaud's disease. Issue 1 (1st January 2018) - Şahin, Ömer Fatih; Tarıkçı Kılıç, Ebru; Aksoy, Yakup; Kaydu, Ayhan; Gökçek, Erhan
ABSTRACT: Stellate ganglion blockage (SGB) is a method used for treating Raynaud's phenomenon (RP). This study primarily aimed to determine whether the perfusion index (PI) can be used an alternative to Horner's signs in evaluating the efficacy of SGB in patients diagnosed with RP. In a total of 40 patients, aged 18–65 years and diagnosed with primary RP, SGB was applied for 5 days on the same side with the 2-finger method, using 6 mL of 5% levobupivacaine at the 7th cervical vertebra level. The PI values were recorded from the distal end of the 2nd finger of the upper extremity on the side applied with the block at baseline and at 5, 15, 30, 60 and 120 min. The onset time of Horner findings was recorded. The PI values and visual analogue scale (VAS) pain scores were recorded pre-treatment and after 2 weeks.When the PI values of the 40 patients were examined, a 62.7% increase was observed from baseline to the first session at 5 min (p < 0.05). When all sessions were evaluated, a statistically significant increase was determined in the PI values measured at 5, 15, 30, 60 and 120 min compared with the baseline PI values. There was a statistically significant decrease in the post-treatment VAS pain scores and a statistically significant increase in the post-treatment PI values (p < 0.05). By eliminating peripheral vasospasm with the application of SGB in patients with RP, the distal artery blood flow and PI are increased. PI measurement is a more objective method and therefore could be used as an alternative to Horner findings in evaluating the success of SGB. PI is a non-invasive and simple measurement and also an earlier indicator in evaluating the success of SGB than Horner's signs.